Strategi Guru PAI dalam Mengelola Kelas yang Aktif, Efektif, dan Menyenangkan di MAS Jam’iyah Mahmudiyah Tanjung Pura - Novika Afridaini; Diah Ayu Irmadani; Kamaliah R (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
This study aims to explore the role of Islamic Religious Education (PAI) teachers in creating an active, effective, and fun classroom atmosphere at MTs Jam'iyah Mahmudiyah Tanjung Pura. The research method used was qualitative with a case study approach, collecting primary data through in-depth interviews with PAI teachers, students, and other related parties, as well as secondary data from relevant documents. The results showed that PAI teachers applied various strategies in classroom management, including creating positive interactions and using diverse learning techniques to prevent student boredom. The results of observations and interviews revealed that teachers' active participation in the teaching and learning process is essential to maintain students' motivation and engagement. Thus, the role of PAI teachers is not only as teachers but also as facilitators who support the development of students' potential through an interesting and interactive learning environment.